Education on the use of used cooking oil waste into aromatherapy candles for housewives in Terentang III Village - Muh. Fauzi Risa; Berliani Amanda; Choiri Nisa Salsabilah; Safira Vilola; Qomala Khafifah; Putri Yani; Luluul Jannah; Muhammad Fachridho; Rosalia Adisti; Sinta Sinta; Yorenza Meifinda (Universitas Muhammadiyah Magelang, 2023)
This Community Service aims to increase the community's knowledge and skills in utilizing used cooking oil waste into aromatherapy candles. The activity was carried out in the form of a workshop by providing complete instructions, outreach, and practices for processing kitchen waste in the form of used cooking oil into products of economic value for housewives in Terentang III Village, Koba District, Central Bangka Regency. The results of the program succeeded in increasing the knowledge and skills of housewives in utilizing used cooking oil waste into aromatherapy candles.